Perception evaluation of soundscape in a wetland community by spatial graphical representation: a case study of Hangzhou Xixi Wetland, China. - J.R. Shi; Y. Yang; D.S. Wang; H. Liu; X.M. Zhao (International Association of Lowland Technology, 2019)
The perception evaluation of soundscape in a wetland community is investigated based on spatial graphical representation and statistical theory. The data were analyzed by EXCEL and SPSS and they produced the zoning map of soundscape in a wetland park. XIXI Wetland,Hangzhou, China, was chosen as the case area. The perception evaluation of soundscape was conducted at ten aspects: elements, time, preference, integration, liveliness, boisterousness, pleasure, feature, nature and irritability. Meanwhile, the goal is to provide a favorite soundscape for tourists, and a visual map with graphic reference is drawn for soundscape design in the wetland community.